Simultaneously advanced removal of nitrogen and phosphorus in a biofilter packed with ZVI/PHBV/sawdust composite: Deciphering the succession of dominant bacteria and keystone species - Qi Zhou; Sun, Haimeng; Jia, Lixia; Wu, Weizhong (BIORESOURCE TECHNOLOGY, 2022)
In this study, a biofilter was developed with a ZVI/PHBV/sawdust (ZPS) composite for treating simulative secondary effluent from wastewater treatment plants. Results showed that effluent concentrations of NO3–N and TP in the ZPS biofilter were stable below 2.0 mg/L and 0.1 mg/L, corresponding to 95% NO3–N removal and 99% TP removal, respectively. Microbial community analysis revealed that the transformation of dominant taxa from Dechloromonas to Clostridium sensu stricto_7 from 30 d to 120 d suggested that the ZVI-induced succession of dominant fermentation bacteria ensured the stable carbon supply for denitrification. Co-occurrence network analysis showed that the ZVI directly enhanced the interaction of microbial community. Fe-related bacteria occupied a key position in the rare species, which might maintain the function of iron-mediated organic matter decomposition and denitrification. These findings provide an alternative for advanced removal of nitrogen and phosphorus in biofilters packed with ZPS composites.